Improving Trade and Transport for Landlocked Developing Countries : World Bank Contributions to Implementing the Almaty Programme of Action - World Bank (Washington, DC, 2014)
A ministerial intergovernmental conference in pursuit of these commitments was held in August 2003 in Almaty, Kazakhstan. The conference agreed to the Almaty Programme of Action (APoA), calling for joint efforts by transit and landlocked countries-with substantial technical and financial assistance from other countries-to revise their regulatory frameworks affecting trade movements and to improve their trade-related infrastructure. The two World Bank strategies and the APoA have the same overarching objective: to support the countries targeted by the proposed objectives and actions, in order to achieve inclusive and sustainable development. The report is divided into six sections. Section one provides a comparison of Landlocked Developing Countries (LLDCs) and transit countries in terms of trade performance. It particularly focuses on the growth of total trade and Gross Domestic Product (GDP) per capita in light of trade openness and export diversification. This is followed in section two by an assessment of logistics performance and trade costs of landlocked countries, and their transit and coastal neighbors, on the basis of the Logistics Performance Index (LPI). The operational challenges for traders in LLDCs, including unreliable supply chains and delays, as well the underlying causes, are discussed in section three. Section four then focuses on the various activities of the World Bank to address the key priorities of the Almaty programme, with a focus on regional integration and trade facilitation. In continuation, section five highlights some of the regional integration and trade facilitation projects and initiatives that are being implemented. The report concludes by re-emphasizing the continued validity of several of the original APoA priorities for financial and technical assistance, in the context of the World Bank's overall strategic goals (section six).